Vremja reakcii kak pokazatel' koordinacionnoj sloznosti fiziceskogo upraznenija - Orlova, N. A. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The object of the research was the definition of the dependence of the latent period of motion reaction from the coordination complexity of motors component. The registration of the time of reaction realized by the electrical chronometer with the minimal interval in 1 ms. 18-22 athletes, who had different qualification and specialization participated In the experiment. The time of reaction increase with the enlargement of the difficulty of physical exercises. The difficulty of physical exercises define to the structure and volume of the motions programs, to the degrees of coordination working programs, to the quantity changes of direction in the joint, to the size of external weight, to the muscles moments of starting positions. The regularity of the coordination complexity of motions activity was used for basing the means of physical and technical preparation in the V.I. Alekseev's athletics school.